CLINICOHISTOLOGICAL PATTERN OF OVARIAN TUMOURS IN PESHAWAR REGION - Yasmin, Sumaira; Yasmin, Aiman; Asif, Mohammad (Journal of Ayub Medical College Abbottabad, 2008)
Background: Ovarian tumours are one of the major health problems confronting the general practitioners in general and gynaecologists in particular. Ovarian tumours may either be asymptomatic, found on the routine ultrasound examination or symptoms may be vague till the patient has an acute emergency like torsion or rupture of a benign cyst. The worst is late presentation of a malignant ovarian tumour. There is marked variation in the presentation of the tumour as well as in histological types. This study was undertaken to analyse modes of presentation and various histopathological patterns of ovarian tumours. Methods: This study was conducted from 1st January, 2002 to 31st December, 2002, in Gynaecology ’˜A’ Unit, Lady Reading Hospital (LRH) Peshawar. After admitting patients with ovarian tumours a detailed case history was taken followed by thorough clinical examination. All the relevant details were recorded using the questionnaire. Patients were investigated after performing various surgical procedures; the specimens of ovarian tumours were subjected to Histopathological examination in the histopathology section, Lady Reading Hospital, Peshawar. Results: Amongst the total numbers of 5732 gynaecological admissions during study period the total numbers of ovarian tumours were sixty-eight. Out of which benign ovarian tumours were 61 (89.71%) and malignant ovarian tumours were 7 (10.29%) There were no tumours with borderline malignancy. The commonest histological pattern observed in the study was epithelial tumours (76.5%) including both benign and malignant tumours. The commonest benign tumour was serous cyst adenoma (24%) followed by mature cystic teratoma (18%). Common malignant ovarian tumours were granulosa cell tumours and Endometriod carcinoma (each 28.5%). Conclusion: Epithelial tumours are the commonest variety of ovarian tumours followed by Germ cell tumours. The histological type of ovarian tumour correlates with the prognosis of the tumour. Keywords: Ovarian tumours, teratoma, adenoma, cystadenoma, metastatic, neoplasm